2018
DOI: 10.1126/scirobotics.aaq0076
|View full text |Cite
|
Sign up to set email alerts
|

Mobile nanotweezers for active colloidal manipulation

Abstract: An important goal in nanotechnology is to control and manipulate submicrometer objects in fluidic environments, for which optical traps based on strongly localized electromagnetic fields around plasmonic nanostructures can provide a promising solution. Conventional plasmonics based trapping occurs at predefined spots on the surface of a nanopatterned substrate and is severely speed-limited by the diffusion of colloidal objects into the trapping volume. As we demonstrate, these limitations can be overcome by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 59 publications
0
95
0
Order By: Relevance
“…Thermoplasmonics is an emerging hot topic that offers a route to controllable actuation at the nanoscale and reversible plasmon tuning of sensing devices . The ability to manipulate nanoparticles in order to create and steer nanostructures is essential in many applications such as drug delivery, noninvasive microsurgery, nanoassembly, and fabrication …”
Section: Heating Up the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermoplasmonics is an emerging hot topic that offers a route to controllable actuation at the nanoscale and reversible plasmon tuning of sensing devices . The ability to manipulate nanoparticles in order to create and steer nanostructures is essential in many applications such as drug delivery, noninvasive microsurgery, nanoassembly, and fabrication …”
Section: Heating Up the Environmentmentioning
confidence: 99%
“…Ding et al demonstrated the assembly of light‐induced actuating nanotransducers (ANTs), see Figure a‐i,ii . Such actuators allow the transformation of thermal energy into physical motion, essential to applications in robotics, sensing, storage devices, and smart windows . By binding the temperature‐responsive polymer pNIPAM to charged spherical Au nanoparticles, the authors were able to control the formation of Au clusters under light illumination.…”
Section: Heating Up the Environmentmentioning
confidence: 99%
“…That makes it possible to control the range and magnitude of this kind of interaction in different systems. Adding silver islands to magnetically-driven helical swimmers, Ghosh et al managed to microtrap plasmonically passive particles and use this system for transportation [76]. This elegant system allows very controlled manipulation of one or multiple passive microobjects, as well as transportation.…”
Section: Magnetic Forcesmentioning
confidence: 99%
“…From a fundamental point of view, this work deserves recognition because it proves the robustness of the phoretic interactions in terms of materials, shapes, and sizes. An even more precise control was achieved by Ghosh et al, using mobile optical traps grafted on helical microswimmers [76].…”
Section: Applicationsmentioning
confidence: 99%
“…These efforts are directed toward developing various strategies to induce motility in artificial nanostructures, e.g., using chemical, magnetic, acoustic, electrical fields, or using biohybrid structures, and demonstrating controlled manipulation in different fluids ranging from deionized water to more biologically relevant systems, such as saliva, serum, urine, mucus, peritoneal fluid, and blood . The enhanced motility of the nanomotors was utilized for speedy diagnosis, active transport, and delivery of payloads, all of which are important for medical interventions of the future. These applications are of special relevance when applied to a living biological cell, the building block of life itself.…”
mentioning
confidence: 99%